(untitled) (The University of Nairobi Journal of Language and Linguistics, 2023)
This paper provides evidence from Bari, an Eastern Nilotic language found in the southern Sudan, that not all that are known as ‘Determiners’ are generated in the D-head of DP as has been advocated by Abney (1987) and others. In agreement with Guisti (1992); Guisti and Giuliana (1994) and Szablocsi (1987), the paper argues that ‘determiners’ do not constitute one homogeneous categorial and structural group. It shows that co-occurrence of determiners in DP is due to the fact that these elements are generated in different positions and therefore target different positions within DP. It claims that that is the case because DP, at least in Bari, contains Xmax intermediate projections between D and the complement of NP which hosts the determiners. These intermediate Xmax projections are obligatorily selected each time the modified head N selects a modifier. The paper further claims that the heads of these projections, including the D-head of DP, are null and that the so-called determiners and other modifiers such as adjectives are base-generated in Spec-positions in DP and other embedded complement projections within DP. These null heads are targets of N movement of the modified head noun which rises head-to-head, triggering widespread Spec-Head agreement within DP and other complement projections embedded in DP. Since the determiners are generated in Specprojections, this Spec-head relation, the paper argues, accounts for why a modifying determiner or adjective agrees in number and gender with the head noun it modifies.